The Structural Integrity of Carbon Fiber Composites Fifty Years of Progress and Achievement of the Science, Development, and Applications - Beaumont, Peter W. R.; Soutis, Constantinos; Hodzic, Alma.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book brings together a diverse compilation of inter-disciplinary chapters on fundamental aspects of carbon fiber composite materials and multi-functional composite structures: including synthesis, characterization, and evaluation from the nano-structure to structure meters in length. The content and focus of contributions under the umbrella of structural integrity of composite materials embraces topics at the forefront of composite materials science and technology, the disciplines of mechanics, and development of a new predictive design methodology of the safe operation of engineering structures from cradle to grave. Multi-authored papers on multi-scale modelling of problems in material design and predicting the safe performance of engineering structure illustrate the inter-disciplinary nature of the subject. The book examines topics such as Stochastic micro-mechanics theory and application for advanced composite systems Construction of the evaluation process for structural integrity of material and structure Nano- and meso-mechanics modelling of structure evolution during the accumulation of damage Statistical meso-mechanics of composite materials Hierarchical analysis including "age-aware," high-fidelity simulation and virtual mechanical testing of composite structures right up to the point of failure. The volume is ideal for scientists, engineers, and students interested in carbon fiber composite materials, and other composite material systems.
Part I -- 1 50 years of carbon fibre 60 years in composite materials -- 2 But how can we make something useful out of black string?" The development of carbon fibre composites manufacturing 1965-2015 -- 3 Boron Fiber to Carbon Fiber -- 4 Serendipity in Carbon Fibres Interfaces and Interphases in Composites -- Part II -- Nano-engineered hierarchical carbon fibres and their composites preparation, properties, and multi-functionalities -- 5 Nano-engineered carbon fibre reinforced composites challenges and opportunities -- 6 A Nano-Micro-Macro Multi-Scale Model for Progressive Failure Prediction in Advanced Composites -- 7 Carbon fibre reinforced polymer laminates with nanofiller enhanced multi-functionality -- 8 Analysis models for polymer composites across different length scales -- 9 Analysis models for polymer composites across different length scales -- Part III -- 10 Microscale characterization techniques of Fibre Reinforced Polymers -- 11 Fibre Distribution and the Process Property Dilemma -- 12 Analysis of defect developments in composite forming -- Part IV -- 13 Deformation Mechanisms of Carbon Fibres and Carbon Fibre Composites -- 14 Micromechanical evidences on inter-fibre failure of composites -- 15 Progressive Damage in Fibre-Reinforced Composites Towards more Accurate and Efficient Computational Modelling and Analysis -- 16 Predicting properties of undamaged and damaged carbon fibre reinforced composites -- Part V -- 17 Composites Toughen up ! -- 18 Slow cracking in composite materials catastrophic fracture of composite structures -- 19 Finite fracture mechanics a useful tool to analyze cracking mechanisms in composite materials -- 20 Traction-separation relations in delamination of layered carbon-epoxy composites under monotonic loads Experiments and Modeling -- 21 Damage and failure analysis of bolted joints in composite laminates -- 22 City Cars made from Composites -- Part VI -- 23 A virtual testing approach for laminated composites based on micromechanics -- 24 Virtual testing of composite structures Progress and challenges in predicting damage, residual strength and crashworthiness -- 25 Contribution of virtual simulation to industrialisation of carbon fiber reinforced polymer composites for manufacturing processes and mechanical performance -- Part VII -- 26 Multi scale progressive failure modeling from Nano-structured carbon fibers to textile composites -- 27 Textile Structural Composites - from 3-D to 1-D fiber architecture -- 28 Experimental and Multiscale Numerical Studies of Woven Fabric Carbon Composite Cylinder Subjected to Internal Pressure Loading -- Part VIII -- 29 Fatigue of 2D and 3D carbon-fiber-reinforced polymer matrix composites and of a unitized polymer/ceramic matrix composite at elevated temperature -- 30 Carbon Fibers in Tribo-Composites.
Keywords: Ceramic materials; Materials -- Analysis; Ceramics; Characterization and Analytical Technique